The Effectiveness of Village Fund (Dana Desa) Allocation for Sustainable Development Projects: A Survey of Village Government Officials - Ngr. Putu Raka Novandra Asta; Sun Wei; Kanti Aldino Hadi (Yayasan Adra Karima Hubbi, 2025)
Background. Efforts to promote sustainable development in rural Indonesia increasingly rely on Village Fund (Dana Desa) allocations, which are intended to support local infrastructure, environmental management, and community empowerment. Despite substantial fiscal transfers from the national government, concerns persist regarding whether these funds are effectively translated into sustainable development outcomes. Many villages continue to face challenges related to planning quality, administrative capacity, environmental degradation, and accountability mechanisms. Purpose. This study aims to evaluate the perceived effectiveness of Village Fund allocation in supporting sustainable development projects, with a specific focus on environmental initiatives, social welfare programs, and economic empowerment activities. The research also seeks to identify key institutional, administrative, and governance factors that influence program success at the village level. Method. A quantitative survey design was employed, involving 214 village government officials from multiple districts. Respondents were selected using stratified sampling to ensure representation across geographical areas and administrative categories. Data were collected through structured questionnaires measuring fund management practices, project outcomes, and perceived challenges, and were analyzed using descriptive statistics and multiple regression. Results. Findings indicate that Village Fund allocation is moderately effective in promoting sustainable development, particularly in infrastructure and community-based economic projects. Environmental projects show weaker outcomes due to limited technical expertise and inadequate long-term planning. Regression analysis reveals that transparency, participatory planning, and administrative capacity significantly predict program effectiveness. Conclusion. The study concludes that strengthening governance capacity and integrating sustainability criteria into village planning can enhance the long-term impact of Village Fund programs.